First Report of Heterodermia squamulosa (Lichenized Ascomycota, Physciaceae) in South Korea - Wang, Xin Yu (The Korean Society of Mycology, 2008)
Heterodermia squamulosa (Degel.) W.L. Culb. was found in the mountain of Gariwang, Gangwon province, in 2008. It is characterized by numerous squamules along the margin, decorticate and white lower surface, rhizines along the margin, black and densely squarrosely branched, usually forming a dense mat under the thallus. Apothecia margins densely squamulose, ascospores 12~15 × 25~30 µm. Atranorin and zeorin contained in thallus. This is the first record of this species in South Korea.